Botryane Sesquiterpenoids, Cyclopentadepsipeptides, Xanthones, and Trichothecenes from Trichoderma oligosporum - Chen, Baosong; Li, Erwei; Liu, Li; Liao, Mingfang; Zhu, Zhaoxiang; Zhuang, Wenying; Bao, Li; Liu, Hongwei (Planta Medica, 2018)
Five new botryane sesquiterpenes (1–5), one new cyclopentadepsipeptide (9), and two new xanthones (11 – 12), together with 11 known compounds, were isolated from Trichoderma oligosporum. The structures of the new compounds were identified by comprehensive spectroscopic methods including nuclear magnetic resonance and mass spectrometry. The cytotoxicity of 1–19 was evaluated against K562, A549, and ASPC cell lines. Compounds 5, 8, 11, 17, and 18 showed cytotoxicity against the K562 cell line with more than 50% inhibition at 12.5 µM. As to A549 cell line, compound 8 showed the strongest cytotoxicity with approximately 50% inhibition at 25.0 µM. No compounds showed cytotoxicity against the ASPC cell line.
Keywords: Trichoderma oligosporum; Hypocreaceae; botryane sesquiterpenoids; cyclopentadepsipeptides; xanthones; trichothecenes